Hydrodynamics and Mineral Beneficiation Efficiency of Ionic Microbubble - Parmar, Rajeev (My University, 2016)
Microbubble aided flotation has been widely employed in the various fields for the process intensification. They have been used for recovery of proteins, recovery of microorganism, removal of heavy metal ions from water, removal of dye and pigment. So an interest was felt to study the stability, rheology, dispersion characteristics of microbubble suspension in order to use them for the mineral beneficiation. Based on the present status of research, this work was undertaken with the following objectives: Study the hydrodynamics such as rheology, pressure drop and friction factor of microbubble-suspension flow. Development of mechanistic model to analyze the interfacial stress of microbubble suspension flow considering the bubble formation, drag at interface and loss of energy due to wettability. Study the terminal rise velocity, microbubble size distribution and stability of microbubble. Development of correlations to interpret the bubble size and stability of microbubble. Investigation of the dispersion characteristic of ionic microbubble suspension in continuous plant prototype. Development of phenomenological model with consideration of liquid circulation to analyze the dispersion coefficient of the microbubble suspension. Study the mineral beneficiation by ionic microbubble in continuous plant prototype. Development of phenomenological kinetic model based on mixing, collision, attachment and detachment mechanisms of fine particles.
Majumder, Subrata K
Keywords: CHEMICAL ENGINEERING